2+7(x-5)=9-7(x-5)

Simple and best practice solution for 2+7(x-5)=9-7(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+7(x-5)=9-7(x-5) equation:


Simplifying
2 + 7(x + -5) = 9 + -7(x + -5)

Reorder the terms:
2 + 7(-5 + x) = 9 + -7(x + -5)
2 + (-5 * 7 + x * 7) = 9 + -7(x + -5)
2 + (-35 + 7x) = 9 + -7(x + -5)

Combine like terms: 2 + -35 = -33
-33 + 7x = 9 + -7(x + -5)

Reorder the terms:
-33 + 7x = 9 + -7(-5 + x)
-33 + 7x = 9 + (-5 * -7 + x * -7)
-33 + 7x = 9 + (35 + -7x)

Combine like terms: 9 + 35 = 44
-33 + 7x = 44 + -7x

Solving
-33 + 7x = 44 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-33 + 7x + 7x = 44 + -7x + 7x

Combine like terms: 7x + 7x = 14x
-33 + 14x = 44 + -7x + 7x

Combine like terms: -7x + 7x = 0
-33 + 14x = 44 + 0
-33 + 14x = 44

Add '33' to each side of the equation.
-33 + 33 + 14x = 44 + 33

Combine like terms: -33 + 33 = 0
0 + 14x = 44 + 33
14x = 44 + 33

Combine like terms: 44 + 33 = 77
14x = 77

Divide each side by '14'.
x = 5.5

Simplifying
x = 5.5

See similar equations:

| 3(6x+2)=9(2x-2) | | -a/6-(31)=64 | | Z^2-2z+11=0 | | 5x^5+9x^3-x+1=0 | | 9=4g-3 | | 12y-8y=32 | | 5x^2-269=51 | | 13+2.50h=11+3.75h | | (s+4)(s-3)=0 | | 4x+5x+9=16 | | 232=75-w | | Log(9)(x^2-6)=Log(9)(30) | | c=108x^2+108xy^2 | | -7-2x=-4 | | 4k(k+5)=0 | | 19-4j=11 | | 14=8+3k | | 5*x^3-3*x^2+8=0 | | 2r(r-4)=0 | | 12-4x-9-3x= | | 3/4x-1/2=181/4 | | 2-4x-9-3x= | | 5*x^3-3*x^2-8=0 | | 4x-5(2x-9)=6(x+5)+3 | | 10+3h=19 | | c=(6x+6y^2)18x | | 2(x-6)+4x+7=43 | | 3x-10=8x-20 | | 100=-4w-20 | | 8-5y=-27 | | 2[c+4]=3[c+5] | | 1-r=-s |

Equations solver categories